2022
DOI: 10.1007/s00262-022-03208-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension reported with immune checkpoint inhibitors: a pharmacovigilance study

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, we did not conduct separate analyzes on different ICIs, and there may be differences in PAD/AoD ratio progression among different ICIs. It has been reported that 50% of patients identified with immune-related PAH were treated with nivolumab ( 48 ). However, we randomly collected real-world patients with NSCLC treated with different ICIs, and the results are hence considered more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not conduct separate analyzes on different ICIs, and there may be differences in PAD/AoD ratio progression among different ICIs. It has been reported that 50% of patients identified with immune-related PAH were treated with nivolumab ( 48 ). However, we randomly collected real-world patients with NSCLC treated with different ICIs, and the results are hence considered more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Another explanation may also lie in the common risk factors in patients with lung cancer who were prone to develop major cardiovascular adverse events or pulmonary hypertension following ICI treatment. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…In a pharmacovigilance study, 42 PH (including 11 PAH, 1 PVOD) were identified of which half of cases were associated with nivolumab use [ 89 ]. These cases occurred a median of 77.0 days from initiation of therapy; 31% were fatal [ 89 ].…”
Section: Immunotherapy and Pulmonary Hypertensionmentioning
confidence: 99%
“…In a pharmacovigilance study, 42 PH (including 11 PAH, 1 PVOD) were identified of which half of cases were associated with nivolumab use [ 89 ]. These cases occurred a median of 77.0 days from initiation of therapy; 31% were fatal [ 89 ]. In a study of 59 patients with lung cancer treated with nivolumab, there was an increase of pulmonary artery to aorta diameter, a marker of PH, on computed tomography (CT) imaging from 0.82 to 0.87 ( p 0.001) [ 90 ].…”
Section: Immunotherapy and Pulmonary Hypertensionmentioning
confidence: 99%